2018
DOI: 10.1080/20426445.2018.1506606
|View full text |Cite
|
Sign up to set email alerts
|

Wood properties of Larix sibirica naturally grown in Tosontsengel, Mongolia

Abstract: The wood properties were examined for Larix sibirica naturally grown in Tosontsengel, Mongolia. The dynamic Young's modulus of the logs ranged from 6.31 to 9.65 GPa. The mean values of wood properties were as follows: water-extracted basic density = 0.44 g cm −3 , air-dry density = 0.59 g cm −3 , shrinkage at 1% moisture content change in the radial and tangential directions = 0.18% and 0.32%, modulus of elasticity = 11.24 GPa, modulus of rupture = 102.4 MPa, compressive strength parallel to the grain = 53.1 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
6
11
1
Order By: Relevance
“…The mean SS was higher than that of L. sibirica planted in Finland 9 and L. kaempferi planted in Japan 24 . In the radial variation, similar radial trends were found in L. sibirica that grow naturally in Mongolia 27 and in L. kaempferi planted in Japan 22 .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The mean SS was higher than that of L. sibirica planted in Finland 9 and L. kaempferi planted in Japan 24 . In the radial variation, similar radial trends were found in L. sibirica that grow naturally in Mongolia 27 and in L. kaempferi planted in Japan 22 .…”
Section: Discussionsupporting
confidence: 71%
“…These results indicated that the effect of cold-or hot-water extractives on wood density might be greater in L. sibirica compared to other Larix species. www.nature.com/scientificreports/ Ishiguri et al 27 reported that radial shrinkage at 1% moisture content change showed almost constant values from pith to bark, whereas tangential shrinkage increased up to 4 cm from pith and then became constant at around 0.3%. The mean values and radial variation patterns examined in this study for shrinkage in both the radial and tangential directions in L. sibirica were similar to those of L. sibirica examined by Ishiguri et al 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relationships between wood density and MOR might be affected by presence of large amounts of arabinogalactan in the species. In the previous study [26], we reported that arabinogalactan might be included in hotwater extracts in heartwood of L. sibirica, and the content of hot-water extracts was 14.1%. Thus, it is considered that wood density including arabinogalactan in this species resulted in overestimation of wood density values.…”
Section: Correlations Between Lumber Propertiesmentioning
confidence: 85%
“…In Mongolia, Siberian larch (Larix sibirica Ledeb.) is a major softwood species, and wood from this species is mainly used for structural lumber in construction due to its high mechanical strength properties [18,19,26]. We previously examined the geographical variations of wood properties and the quality of dimension lumber (2 by 4 lumber) for L. sibirica collected from five different provenances in Mongolia.…”
Section: Introductionmentioning
confidence: 99%